THE MEDIATING ROLE OF GOVERNANCE, RISK MANAGEMENT, AND COMPLIANCE IN THE RELATIONSHIP BETWEEN ACQUISITION AND FINANCIAL PERFORMANCE: EVIDENCE FROM KB BANK INDONESIA - Rumapea, Nelly Evalyna; Ermawati, Wita Juwita; Suprayitno, Gendut (LPPM Universitas Jambi, 2026)
Acquisitions are an important bank restructuring strategy for overcoming financial distress; however, their direct contribution to financial recovery remains unclear. This study examines the acquisition of Bank Bukopin by KB Kookmin Bank in 2020 and its effect on the financial performance of both institutions. The research also investigates governance, risk management, and compliance (GRC) as mediating variables in the relationship between acquisition and financial performance. A mixed-method approach was employed using secondary financial data from the periods before the acquisition (2018–2020) and after the acquisition (2021–2024), analyzed through paired t-tests, alongside primary survey data collected from 65 bank employees and analyzed using SEM-PLS. The findings reveal that the acquisition did not have a direct significant effect on profitability indicators, particularly Return on Assets (ROA) and Operating Expenses to Operating Income (BOPO). However, mediation analysis demonstrates that compliance significantly mediates the relationship between acquisition and financial performance, whereas governance and risk management do not show significant mediating effects. These results indicate that immediate post-acquisition financial improvement depends more on the implementation of strong compliance mechanisms than on governance structures alone. The novelty of this study lies in decomposing the GRC framework and identifying compliance as the primary driver enabling acquisitions to achieve financial turnaround. While compliance functions as an immediate operational mechanism for financial recovery, governance and risk management appear to contribute more gradually over time. Therefore, post-merger integration strategies should prioritize strengthening compliance systems to accelerate financial performance improvement.